Implementing Success Management in an IT project - Varajão, João (2018)
Given the high importance and complexity of the evaluation of Information Technology (IT) projects, it is essential that companies define and implement systematic processes for managing success aiming to improve project management and deliverables performance. This article presents the first stage of the implementation of a success management process in an IT project of a large multi-national company. Preliminary results show that, with a small increase of the management effort, this enables a precise definition of what really means success in the context of a project, a better understanding of the different perspectives of the participating stakeholders, a greater focus in what is most important for achieving the project success, the unbiased identification and definition of criteria for evaluating success, and the definition of milestones to carry out the evaluation.